PENGELOLAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. TIRTA INVESTAMA DANONE-AQUA WONOSOBO DI KELURAHAN KEJIWAN KABUPATEN WONOSOBO - Pamungkas Putri, Dinda Nadia; Adnan, Muhammad - (Journal of Politic and Government Studies, 2024)
This research aims to explain and analyze the management of Corporate Social Responsibility (CSR) at PT Tirta Investama Danone-AQUA as one of AQUA Group’s Bottled Drinking Water factories operating in Kejiwan Village, Wonosobo Regency. This research uses a descriptive qualitative approach with data collection techniques in the form of indepth interviews and observations. The results were analyzed using CSR theory, governance theory, legitimacy theory, stakeholder theory, and community participation theory. The results showed that three important actors, namely PT Tirta Investama, Kejiwan Local Government, and the Institute for Rural Technology Development of Wonosobo, were involved in the CSR management in Kejiwan Village. Stakeholders engagement contributes to corporate legitimacy by building community support, promoting trust between government and the community, and encouraging community members to participate in public service. The conclusion of this research is that the collaboration among the three CSR management actors creates a needs-based and targeted program. However, the process of monitoring and accountability of CSR programs has not been implemented optimally and is only a formality. Therefore, the company and other stakeholders need to ensure that the implementation of CSR programs leads to community independence and is able to apply it in a wider community network